Detection Of Salmonella Typhimurium In Livestock Products By Pcr Technique - VIJAYA KUMAR ANUMOLU,; KRISHNAIAH.N,; VENKATESWARA RAO.L, (International Journal of Pharma and Bio Sciences, 2012)
Livestock products were screened for Salmonella spp. and Salmonella typimurium by PCR assay. Two sets of primers derived from inv A gene and fli C gene were employed to standardize the PCR assay for detection of Salmonella spp. and Salmonella typhimurium respectively. Buffered peptone water as primary enrichment broth followed by tetrathionate broth as selective enrichment broth was used in this study. Out of 150 samples of livestock products like milk, meat and fish screened 45 samples were positive for Salmonella spp. and out of these 45 samples, 3 samples were positive for Salmonella typhimurium. Two step enrichment and followed by PCR assay is giving good results than one step enrichment for screening of Salmonella typhimurium in Livestock products. Hence accurate screening of livestock products by above method decreases the number of Salmonellosis cases.